The death of archaeological theory? - Bintliff, J. L. (John L.); Pearce, Mark (Oxbow Books, 2011)
The Death of Archaeological Theory? addresses the provocative subject of whether it is time to discount the burden of somewhat dogmatic theory and ideology that has defined archaeological debate and shaped archaeology over the last 25 years. Seven chapters meet this controversial subject head on, also assessing where archaeological theory is now, and future directions. John Bintliff questions what theory is and argues that archaeologists should be freed from 'Ideopraxists', or those who preach that a single approach or model is right to the exclusion of all others. Marc Pluciennik again questi.